La sanción penal de los conductores ebrios en Colombia : entre las dificultades dogmáticas y la ausencia de una política criminal coherente. (2014)
The motor traffic proposes new challenges to criminal law, which, according to the punitive tendencies so common today, is presented to the Colombian public opinion, by media and legislators, as the only possible solution to counter the high rate of deaths and injuries caused, in particular, by drunk drivers. However, the creation of new offenses or the hardening of existing penalties can hardly contribute to the reduction of these figures; the role of criminal law for such purposes is limited and criminal policy is but one more in the set of public policies called to improve road safety, which is far indeed from being the most effective in this area.